2009
DOI: 10.1083/jcb.200809198
|View full text |Cite
|
Sign up to set email alerts
|

Htm1 protein generates the N-glycan signal for glycoprotein degradation in the endoplasmic reticulum

Abstract: To maintain protein homeostasis in secretory compartments, eukaryotic cells harbor a quality control system that monitors protein folding and protein complex assembly in the endoplasmic reticulum (ER). Proteins that do not fold properly or integrate into cognate complexes are degraded by ER-associated degradation (ERAD) involving retrotranslocation to the cytoplasm and proteasomal peptide hydrolysis. N-linked glycans are essential in glycoprotein ERAD; the covalent oligosaccharide structure is used as a signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
272
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 222 publications
(288 citation statements)
references
References 62 publications
15
272
1
Order By: Relevance
“…Htm1p (Clerc et al 2009) and Ubc7p (Hiller et al 1996). From a biotechnologists' perspective, it is paramount to study these processes under more natural conditions and using real protein substrates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Htm1p (Clerc et al 2009) and Ubc7p (Hiller et al 1996). From a biotechnologists' perspective, it is paramount to study these processes under more natural conditions and using real protein substrates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IgG secretion was increased in the Δalg3 strains, a genotype which is considered not to produce the glycan signal for ERAD. It has been shown that removal of a mannose by Htm1p is required for efficient binding of ERAD targeted proteins to Yos9p (Szathmary et al 2005;Clerc et al 2009). Therefore, this could imply that the slowly folding IgG protein escape from degradation through ERAD in the Δhtm1 background, giving it more time to fold and be secreted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A mannosidaselike protein Mnl1p recognizes a single isomer of Man 8 GlcNAc 2 glycan of misfolded glycoprotein, and cuts off a terminal 1,2-alpha-mannose residue from the C-chain to generate Man 7 GlcNAc 2 glycan (Figure 2 et Jakob et al, 2001;Nakatsukasa et al, 2001). Lectin Yos9p recognizes the generated 1,6-alpha-linked mannose terminal of Man 7 GlcNAc 2 glycan and then accelerates the ERAD (Buschhorn et al, 2004;Clerc et al, 2009;Friedmann et al, 2002;Gauss et al, 2006;Kanehara et al, 2007;Szathmary et al, 2005). In mns1 cells, Man 9 -GlcNAc 2 glycan is not processed to Man 8 GlcNAc 2 because of lack of Mns1p and is not recognized by Mnl1p.…”
Section: Hm-1-resistant Phenotypes Of Mns1 Do Not Participate In Endomentioning
confidence: 99%
“…In mns1 cells, Man 9 -GlcNAc 2 glycan is not processed to Man 8 GlcNAc 2 because of lack of Mns1p and is not recognized by Mnl1p. The 1,6-alpha-linked mannose terminal in N -glycan of alg3 mutant can be recognized by Yos9p (Clerc et al, 2009). Therefore, we assumed that HM-1 resistance of alg3 and mns1 mutants result from abnormal ERAD acceleration of some glycoproteins.…”
Section: Hm-1-resistant Phenotypes Of Mns1 Do Not Participate In Endomentioning
confidence: 99%